KONSEPSI SIWA-BUDDHA DALAM KAKAWIN NILACANDRA - Heri Purwanto; Wedana, I Wayan Bagus Citra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
The complexity of the encounter between Saivism and Buddhism in the Nusantara archipelago is often perceived as a simple phenomenon, whereas it possesses profound theological depth within specific literary texts. This study aims to analyze the theological conception of Siwa-Buddha in the Kakawin Nilacandra. The method employed is qualitative, utilizing a textual study or philological approach through content analysis of the stanzas in the Kakawin Nilacandra. The findings reveal that this text presents a unique perspective on the theological collaboration between Siva and Buddha within cosmology. Divine figures from both traditions are considered essentially equivalent, such as the identification of Hyang Iswara with Amoghasiddhi and Mahadewa with Amitabha. Furthermore, it can be argued that the Siva-Buddha teaching constitutes a well-established and enduring doctrine, as it perceives God’s immanent presence within both natural elements and the human body. Consequently, this doctrine serves as a philosophical foundation for religious harmony that remains relevant to the present day.